Factors Affecting Customer's Intention To Return To The Movie After Reopening During The Covid-19 Pandemic - Meydiana, Kesya; Rifqa, Muhammad; Sapto Raharjo, Titis; Murwani, Ina Agustini (Green Publisher Indonesia, 2022)
Journal this discuss about influencing factors intention customer for return to cinema after reopening during covid-19 pandemic. Study this aim for test influencing factors intention customer for watching at the cinema During period pandemic, when cinema closed almost 8 months long During 2020 and rising the number of OTT platforms is also still development The unsettling COVID-19 pandemic community, plus restrictions also inside building cinema. Method research that we use in research is study quantitative where study this use web-based questionnaire survey method. Population in study this is Indonesian population in Jabodetabek who is at least once one time watching at the cinema During COVID-19 pandemic. retrieval technique sample in study this use purposive sampling technique. As for the results is in study this obtained that Customer Experience variable has significant influence towards Customer Satisfaction and Customer Trust. Then Customer Satisfaction and Customer Trust have significant influence towards Customer Loyalty.